External Ventricular Drainage for Intraventricular Hemorrhage - Dey, Mahua (Curr Neurol Neurosci Rep, 2012)
Hemorrhagic stroke accounts for only 10% to 15% of all strokes; however, it is associated with devastating outcomes. Extension of intracranial hemorrhage (ICH) into the ventricles or intraventricular hemorrhage (IVH) has been consistently demonstrated as an independent predictor of poor outcome. In most circumstances the increased intracranial pressure and acute hydrocephalus caused by ICH is managed by placement of an external ventricular drain (EVD). We present a systematic review of the literature on the topic of EVD in the setting of IVH hemorrhage, articulating the scope of the problem and prognostic factors, clinical indications, surgical adjuncts, and other management issues.